Pengaruh Fasilitas Perabot dan Peralatan Perpustakaan Terhadap Kinerja Pustakawan (Studi pada Peprustakaan Universitas Negeri Malang) - Cahyaningtyas, Dwi Fitrina (Jurnal Administrasi Publik, 2016)
Abstract : The Influence of Librariy Facilities To Librarian Perfomance (Study at Library State University of Malang). In the progress of globalization, the library is faced with the problem of information explosion. The library, as a librarian workplace need to consider aspects of the facility or the infrastructure to support the activities of librarians.  The  research function is to know  is there any influence on the performance librarians performance. In this case using the method of explanatory research with quantitative approach. Technique of collecting the data was questionnaire and interview by distributing questionnaires and interviews. The Sampling selection used saturated sample method of 19 respondents The analytical method used is the method of multiple linear regression. By using multiple linear regression, suggesting the equation Y 30.629 - 3,669X1 + 3,426X2. The F test results showed the number of 13. And the level of significance less than 0.05. It shows that all these variables simultaneously affect the performances of the librarian. In addition the result of T-test shows that variable Affect against the furniture variable on the librarian perfomances, and the equipment variable significantly influence the librarian perfomances. Result Correlation Coefficient (r) in this case  showed a value of  0.801 which is included in the category of very strong.To improve  the quality of librarians perfomances, Library State University of  Malang should be improve the facilities of existing equipment and increase the human resource library science background. Keywords : Globalization, librarians perfomances, library furniture and equipments. Abstrak : Pengaruh Fasilitas Perabot dan Peralatan Perpustakaan Terhadap Kinerja Pustakawan (Studi pada Peprustakaan Universitas Negeri Malang). Ditengah kemajuan era globalisasi, perpustakaan sering kali dihadapi dengan ledakan informasi, salah satunya adalah perpustakaan perguruan tinggi yang melayani seluruh civitas akademik. Perpustakaan sebagai sarana pencerdas kehidupan bangsa  harus mampu memberikan informasi dan jasa terhadap pemustaka. Untuk itu, perpustakaan sebagai tempat kerja pustakawan perlu memperhatikan aspek sarana dan prasarana untuk menunjang kinerja pustakawan. Fasiltas perpustakaan yang baik dan  memadai dapat mempengaruhi kinerja pustakawan. Penelitian menggunakan teknik explanotory research dengan pertimbangan 19 pustakawan sebagai populasi dan sampel serta menggunakan analisis linier berganda. Pengumpulan data menggunakan kuisoner dan wawancara serta diolah menggunakan SPSS 16. Berdasarkan uji parsial, menunjukan variabel fasilitas perabot perpustakaan tidak berpengaruh terhadap kinerja pustakawan, sedangkan untuk variabel fasilitas peralatan perpustakaan berpengaruh secara signifikan terhadap kinerja pustakawan. Kata kunci : Globalisasi, kinerja pustakawan, perabot dan peralatan pustakawan.